2022
DOI: 10.3390/foods11244029
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Extraction of Protein from Pumpkin Seed Press Cake: Impact on Protein Yield and Techno-Functionality

Abstract: Conventional solvent-based methods widely used for isolating plant proteins may deliver an unsatisfactory protein yield and/or result in protein degradation. The present study started with the optimization of pumpkin seed protein from press cake by alkaline extraction and subsequent isoelectric precipitation. Subsequently, extraction was supported by ultrasound under three conditions: ultrasonic treatment followed by alkaline extraction (US+AE), concomitant ultrasonic treatment and alkaline extraction (UAE), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…The isolated pumpkin seed protein has a molecular mass of around 35 kDa (Sert et al ., 2022). HPH treatment had no significant impact on the electrophoresis patterns compared to the control procedure, so that is ensured that HPH up to 150 MPa did not affect the protein's primary structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The isolated pumpkin seed protein has a molecular mass of around 35 kDa (Sert et al ., 2022). HPH treatment had no significant impact on the electrophoresis patterns compared to the control procedure, so that is ensured that HPH up to 150 MPa did not affect the protein's primary structure (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The control procedure was carried out under conditions previously established by Sert et al . (2022). Dispersions of press cake in deionised water (solvent‐to‐solid ratio of 29) were adjusted to pH 11.0 with 0.5 N NaOH and then stirred for 1 h at 500 rpm on a magnetic stirrer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the PDA of mulberry leaf gradually tends to maintain stability. The reason for this phenomenon was that the alkaline condition could increase the protein solubility, but it also could inactive cellulose, which led to an appropriate pH value of 7 [28] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Such as improving the extraction efficiency of raw materials, improving the success rate and possibility of compounding various raw materials, and the development and promotion of new protein-based products. Sert et al [88] abandoned the traditional solvent-based extraction method and used ultrasonic-assisted extraction when extracting pumpkin seed protein, the results showed that ultrasonic treatment could significantly increase the protein yield of isolates. Aarcha and Akalya [89] developed a new plant-based functional beverage and extended its shelf life to 14 days by ultrasound.…”
Section: The Effect Of Multi-field Combination Of Ultrasound On the A...mentioning
confidence: 99%